Structural modeling of the effect of school culture on psychological well-being with the mediating role of narcissism and achievement emotions - maryam fallahi; samaneh salimi (مطالعات روانشناسی تربیتی)
The aim of the present study was to investigate the structural modeling of the effect of school culture on psychological well-being with the mediating role of narcissism and students' progress emotions. The method of this research was structural equation model correlation. The statistical population of this research was all the students of public schools in Ahvaz in the academic year 1402-1401 in the number of 38300, of which 392 were selected by stratified random sampling method. Four standard psychological well-being questionnaires of Riff (1989), school culture by Alexander and Sade (1998), progress excitement by Pakran et al. (2005) and narcissism by Ames et al. (2007) were used to collect data. The obtained data were analyzed using spss23 and Lisrel 8.8 software. The results of data analysis based on regression coefficients show that school culture has a 0.58 effect on psychological well-being, school culture has a 0.71 effect on progress emotions, school culture has an effect on narcissism 0.69, progress emotions have a 0.37 effect on psychological well-being, and narcissism has an effect on 0.71. Psychological well-being has had a significant effect of 0.40. According to the findings of the research, it can be concluded that the school culture has significant effects on the psychological well-being, emotions of progress and narcissism of the students, therefore it is recommended to the school administrators to improve the school culture to the students' communication with each other, the communication of knowledge. Students should pay attention to the teacher and educational opportunities.